1981
DOI: 10.1111/j.1365-2818.1981.tb01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface labelling with gold colloid particulates: the use of avidin and staphylococcal protein A‐coated gold in conjunction with biotin and fc‐bearing ligands

Abstract: SUMMARY Procedures for preparing gold colloid particles stabilized with either avidin or protein A are described. Methods of using these general utility tracers for localizing biotinylated and fc bearing immunoglobulins are outlined and, as examples of the way in which these methods can be applied, procedures for identifying epidermal growth factor receptors and surface fibronectin on ovarian granulosa cells are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The high resolution immunolabelling technique we have used has resulted in the most detailed picture of the molecular organisation of the desmosome so far presented. A previous estimate of the resolution obtainable using this immunolabelling technique has suggested that the maximum possible distance between the gold particle observed and the antigen molecule it is labelling can be no greater than 12 nm (Tolson et al, 1981). We show that the major groups of desmosomal proteins and glycoproteins make distinctly different contributions to desmosomal structure.…”
Section: Discussionmentioning
confidence: 57%
“…The high resolution immunolabelling technique we have used has resulted in the most detailed picture of the molecular organisation of the desmosome so far presented. A previous estimate of the resolution obtainable using this immunolabelling technique has suggested that the maximum possible distance between the gold particle observed and the antigen molecule it is labelling can be no greater than 12 nm (Tolson et al, 1981). We show that the major groups of desmosomal proteins and glycoproteins make distinctly different contributions to desmosomal structure.…”
Section: Discussionmentioning
confidence: 57%
“…sulphated glycoprotein C purified by SDS-gel electrophoresis from RM (Cooper et al, 1981 Vuento and Vaheri (1979 For immunoelectron microscopy, grids were incubated with appropriate antisera dilutions for 2 h at 40C and rinsed on 5% bovine serum albumin (BSA) in PBS. Grids were then incubated with protein A-gold complex (Tolson et al, 1981) for 1 h at 40C and rinsed again in BSA/PBS. For double labelling, sequential incubations in which the first antibody was followed by protein A-gold 12 rnm anid the second antibody was followed by protein A-gold 5 mn, were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the apparent advantages of histochemical methods based on the interaction of avidin with biotin, this system is not used frequently for electron microscopy in conjunction with colloidal gold. Avidin-gold conjugates are not prepared easily and have a tendency towards high nonspecific binding (28,38); streptavidin-gold conjugates, however, are less prone to these problems. In addition, these gold probes appear to be less stable during storage than other gold reagents (such as antibody-gold or protein A-gold); the proteins dissociate from the gold particles leading to the instability of the colloid, the level of labeling is low, and there are difficulties in reciprocating the labeling.…”
Section: The Advantages Of the Sbbg Methodsmentioning
confidence: 99%